SAT0038 Serum B lymphocyte chemoattractant protein 13 (CXCL 13) and musculoskeletal ultrasonographic findings in early rheumatoid arthritis - Baraka, E; Egila, S; Hamad, G; Khalil, M (Annals of the rheumatic diseases, 2017)
BackgroundPatients in clinical remission may continue to have synovitis detected by the musculo skeletal ultrasonography (MSUS).Recently,B-lymphocyte chemoattractant chemokine (CXCL13) has reported to be upregulated and risen to be a possible new marker of disease inflammation in RAObjectivesto detect early synovitis by grey scale and power Doppler MSUS, measure serum levels of CXCL13 and to correlate these levels with both clinical and ultrasonographic disease activity in early RA patientsMethodsRA was assessed by the modified disease activity score (DAS28).Hands and feet plain radiography were evaluated by Laresn score. A semi-quantitative score (0–3) was used to score synovial effusion (SE), synovial proliferation (SP) and power Doppler (PD) signals by MSUS in 6 synovial sites in 3 joints bilaterally: wrist (dorsal radiocarpal recess). 2nd MCPJ (dorsal and palmar side) and knee (suprapatellar recess) according to the European Leauge Against Rheumatism guidelines. A total MSUS score is the sum of scores for SE, SP and PD signals of the six joints in each patient (0–54).Quantitative detection of serum (CXCL13) levels of all subjects was done by ELISA.ResultsThe mean serum CXCL13 values were highly significantly higher in fifty RA patients than in 30 age and sex matched control subjects with a mean of (388.86±283.63 pg/ml) and (62.96±32.5 pg/ml) respectively (p<0.001) and were significantly positively correlated with morning stiffness durations (p<0.001), Tender Joint Counts (p<0.001), Swollen Joint Counts (p<0.001), VASs (p<0.001), ESR 1st h values (p<0.001) and the platelets count (p<0.05), negatively correlated with disease durations (p<0.05) and HB concentrations (p<0.05) and showed no differences according to presence of extra-articular manifestations or CRP, RF or ACCP seropositivity.(p>0.05). In our RA patients' group, MSUS detected either synovial effusion and /or synovial hypertrophy with or without PD signal in 132 (65%) joints out of 203 clinically silent joints and and detected erosions in 93/300 joints (31%) compared to 27/300 joints (9%) detected by x ray.the serum CXCL13 levels were highly significantly positively correlated with the total MSUS score for each patient (p<0.001),SP and SE gradings (p<0.001) and (p<0.05) and were significantly higher in RA patients with MSUS detected erosions but were not correlated with either PD gradings (p=0.11) or Larsen scores (p>0.05).ConclusionsMSUS is more sensitive than clinical assessment and conventional radiology in detecting synovitis and erosions in RA. Serum CXCL13 levels correlated with MSUS and DAS 28 scores and can be used as a marker for activity and severity of RA.Screening early RA patients by MSUS for more precise evaluation of synovitis activity, severity and better management of the disease and follow up patients to detect if elevated CXCL13 affect RA disease progression or patient disability are recommended.References Naredo E, Valor L, De la Torre I, Martinez-Barrio J, Hinojosa M, Aramburu F, et al., (2013): Ultrasound joint inflammation in rheumatoid arthritis in clinical remission: how many and which joints should be assessed? Arthritis Care Res.;65.Perricone C, Ceccarelli F, Modesti M, Vavala C, Di Franco M, Valesini G, et al., (2012): The 6-joint ultrasonographic assessment: a valid, sensitive-to-change and feasible method for evaluating joint inflammation in RA. Rheumatology; 51(5):866–73. Disclosure of InterestNone declared